Impact of Instrumental and Social- Psychological Beliefs on Customer Satisfaction with Online Product Recommendations - Sulaiman, Ainin; Ashraf, Muhammad; Jaafar, Noor Ismawati (Asian Journal of Business and Accounting, 2016)
Manuscript type: Research Paper Research aims: Online product recommendations (OPRs) provide various benefits for customers in evaluating and selecting a product. A relatively low OPRs usage rate indicates that customers are not satisfied with the performance of the OPRs. This study, therefore, aims to examine the role of instrumental beliefs (i.e. perceived ease of use and usefulness) and social-psychological belief (i.e. perceived confirmation) in predicting and explaining customer satisfaction with the OPRs. Design/ Methodology/ Approach: A hypotheses-deductive approach is employed. The research model is tested by analysing the data of 626 existing users of OPRs which were collected via an online survey. Research findings: Results suggest that instrumental and socialpsychological beliefs are significant contributors to customer satisfaction with OPRs. Additionally, customer expectationconfirmation also positively influences perceived ease of use and OPRs usefulness. Theoretical contribution/ Originality: No prior study has examined the role of instrumental beliefs (i.e. perceived ease of use and usefulness) and social-psychological belief (i.e. perceived confirmation) in predicting customer satisfaction with the OPRs. This study has successfully tested the relationships which are likely to ensure a stable theory development. Practitioner/ Policy implications: Since majority of the respondents were from western countries, the findings would be useful to e-retailers in Asia who are targeting or intending to penetrate the global market, in particular, Amazon customers. Practitioners should adopt a twofold strategy: (a) to inform new customers about the potential benefits of OPRs in terms of its ease of use and usefulness; and (b) to educate old customers on how to use OPRs effectively so as to maximise expectation-confirmation and satisfaction. Research limitations/ Implications: This study employs a crosssectional design rather than a longitudinal design. However, given that the objective of this study is to examine the impact of instrumental and social-psychological beliefs on customer satisfaction, a cross-sectional design is deemed more suitable. The outcome of this study suggests that cultural differences need to be considered when e-retailers are thinking of making such implications on Asian online customers as majority of the respondents in the current study were from non-Asian countries. Keywords: Ease of Use, Expectation-Confirmation, Online Product Recommendations, Satisfaction, Usefulness JEL Classification: M3